Restricted Export Flexibility and Risk Management with Options and Futures - Axel F. A. Adam-Müller; Kit Pong Wong (University of Konstanz, Center of Finance and Econometrics (CoFE), 2002)
This paper examines the production, export and risk management decisions of a risk-averse competitive firm under exchange rate risk. The firm is export flexible in allocating its output to either the domestic market or a foreign market after observing the exchange rate. Export flexibility is restricted by certain minimum sales requirements that are due to long-term considerations. Currency options are sufficient to derive a separation result under restricted export flexibility. Under fairly priced currency futures and options, full hedging with both instruments is optimal. Introducing fairly-priced currency options stimulates production provided that the currency futures market is unbiased.
urn:nbn:de:bsz:352-opus-8201
Keywords: F31; D21; D82; 330; restricted export flexibility; risk management; currency futures; currency options; Währungsmanagement; Export; Entscheidung; Hedging; Devisenoption; Theorie